Droplet dynamics in mini-channel steam flow condensation - Chen, Xi (Kansas State University, 2017)
Power plants are significant water users, accounting for 15% of water withdrawals worldwide. To reduce water usage, compact condensers are required to enable air-cooled condensers and reduce infrastructure costs. Steam flow condensation was studied in 0.952-mm and 1.82-mm hydraulic diameter mini-gaps in an open loop experimental apparatus. The apparatus was validated with single-phase flow. Flow condensation experiments were conducted for a wide range of steam mass fluxes (i.e., 35–100 kg/m²s) and qualities (i.e., 0.2–0.9) in hydrophilic copper and hydrophobic Teflon-coated channels. Water contact angles were 70° and 110° on copper and Teflon, respectively, and in general, filmwise condensation was the primary condensation mode in the hydrophilic channel and dropwise condensation was the primary mode observed in the hydrophobic channel. Pressure drops were reduced by 50–80% in the hydrophobic channels. Condensation heat transfer was enhanced by 200–350% in hydrophobic mini-gaps over hydrophilic mini-gap due to dropwise condensation. Droplet dynamics (e.g., nucleation, coalescence and departure) were quantified during dropwise condensation. A model was created which includes droplet adhesion and drag forces for droplet departure diameters which were then correlated to heat transfer coefficients. An overall mean absolute error of 9.6% was achieved without curve fitting. Noncondensable gases can reduce heat transfer in industrial systems, such as power plants due to the additional layer of thermal resistance from the gas. Condensing steam-nitrogen experiments were conducted for nitrogen mass fractions of 0–30%; the addition of nitrogen reduced heat transfer coefficients by up to 59% and 30% in hydrophilic and hydrophobic mini-gaps, respectively. It was found that during dropwise condensation, the noncondensable layer was perturbed by cyclical droplet motion, and therefore heat transfer coefficients were increased by 2–5 times compared with filmwise condensation of the same mass fraction of nitrogen.
Keywords: Droplet dynamics; Steam condensation; Heat transfer